Auditing and organization of financial statements in the context of sustainable development: A comparative study on GRI and IFAC - Uvakbayeva, Gaukhar; Kogut, Oksana Yu.; Akbalik, Mehtap; Çaliyurt, Kıymet Tunca (International Journal of Innovative Research and Scientific Studies, 2025)
The purpose of this study is to identify the added value of differentiation between the reporting standards developed by GRI and IFAC. It examines global approaches to financial reporting and auditing processes aimed at achieving sustainable development goals. It also aims to raise awareness of countries’ current implementation of the principles of these two organizations. The standards developed by GRI and IFAC were comparatively examined, and countries’ practices based on these two organizations were analyzed. This research relies on a qualitative assessment of existing literature. The analysis indicates that GRI and IFAC adopt divergent strategies when addressing sustainability. Originality of the Research: This study is one of the rare studies that directly compares GRI and IFAC standards regarding the auditing of financial statements within the framework of sustainable development. Furthermore, the practical implications of theoretical knowledge were evaluated by examining practices in different countries. Theoretically, the article advances previous studies by comparing relevant fields and presenting their roles in the global arena. Results: The research revealed significant structural differences between the GRI and IFAC’s sustainability approaches and perspectives on financial auditing. Countries’ practices vary in their level of adoption of these organizations’ standards. This highlights the need for harmonization of global reporting and auditing standards. While GRI determines the content of reporting, IFAC ensures its reliability and accuracy. Considering both structures together is critical for establishing a robust financial reporting and auditing system that serves sustainable development. Conclusion: This study highlights the benefits of sustainable development while also demonstrating the need for auditing and financial statements to keep pace with global change.